Strategy Management Plan for IT Services at PPTI Stikom Surabaya using ITIL Version 3 - Hodianto, Randy; Sutomo, Erwin; Sunarto, Dewiyani (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
Development and Application of Information Technology (PPTI) is one of most important business unit in Institut Bisnis dan Informatika Stikom Surabaya (Stikom Surabaya). PPTI take care all of the data and information that got in Stikom Surabaya, and given to the civitas using IT Services. In order to give services, there are several things that may occured and will disturb the IT Services. PPTI doesn’t have any tactic and strategy to take care of IT Services. So, PPTI need to formulation about strategy and tactic in order to know more about the IT Services. Using the Strategy Management of IT Services of Information Technology Infrastructure Library (ITIL), PPTI could formulate anything about IT Services that they are need to give to the civitas and PPTI could know how to offer the IT Services to give satisfying results. This research will produce a document that consist of IT Services policy, Strategy to support IT Services, and IT Services that are given to the civitas.